Trilce and España, aparta de mí este cáliz: The Word and the Idea of Freedom in Vallejo (and a Possible Correspondence with Sade) - Márquez Arreaza, Dionisio (2024)
This essay studies two works by César Vallejo and, in a complementary manner, a possible correspondence with the Marquis de Sade. In Trilce (1922), the crisis of language is studied through the verbal construction, the eschatological theme and the creation-destruction dialectic based on prison experience. The verbal rupture “frees” the imprisoned poet from jail. In España, aparta de mí este cáliz (1939), the transformation of the cadaver into a project for life is studied from a triple discourse that combines the poetic, the political and the religious in favor of the Spanish republican revolutionary movement. The comparison between the popular God-believing intellectual of the twentieth century and the dix-septièmiste aristocratic-revolutionary pornographer shows two poets of the obscure side of modernity.